Perjanjian Kredit Hak Cipta Sebagai Obyek Jaminan Fidusia di Kota Medan - Tarmizi Tarmizi (Law Studies and Justice Journal (LAJU), 2024)
Banks as banking institutions require collateral (collateral) in providing credit to the public, and until now fiduciary is the type of guarantee binding that is most in demand by the people of Indonesia. Provisions of Law No. 28 of 2014 concerning Copyright, namely Article 16 paragraph 3 states that "copyright can be used as an object of fiduciary guarantee", but in banking practice in Medan City, there has not been a credit agreement where copyright is used as collateral in granting credit. This is because there are factors that hinder the implementation of the credit agreement with the copyright guarantee, which is related to the valuation in the form of money.